Approximation Properties of the Strong Difference Operators - Al-Saidy, S. K.; Hamood, A. A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this paper , we study some approximation properties of the strong difference and study the relation between the strong difference and the weighted modulus of continuity